2014
DOI: 10.1166/jnn.2014.8262
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Silver and Gold Nanoparticles in Enhancing Luminescence of Europium Complexes

Abstract: The influence of 12 nm spherical silver nanoparticles (AgNPs) and 20 nm spherical gold nanoparticles (AuNPs) on the luminescence of europium complex Eu(TTFA)3 were studied. When 350 nm is chosen as the incident light, the maximum enhancement factor of the complexes mixed with AgNPs is about 2.5 at the wavelength of 612 nm. Besides the enhancement of the localized field, the overlap between the localized surface plasmon resonance spectra of nanoparticles and the absorption band of fluorescent molecules is anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…11 shows that both absorption spectra of Ag-HMS and Au-HMS overlapped with the fluorescence emission spectrum of rhodamine derivative R at about 580 nm. In this case an enhancement occurs when both the excitation and the fluorescence signals are near the LSPR peak [46,47]. Furthermore, the LSPR absorption band of Ag-HMS was much wider than that of Au-HMS.…”
Section: Metal-enhanced Fluorescence Effect Of Hms-ag-r and Hms-au-rmentioning
confidence: 96%
“…11 shows that both absorption spectra of Ag-HMS and Au-HMS overlapped with the fluorescence emission spectrum of rhodamine derivative R at about 580 nm. In this case an enhancement occurs when both the excitation and the fluorescence signals are near the LSPR peak [46,47]. Furthermore, the LSPR absorption band of Ag-HMS was much wider than that of Au-HMS.…”
Section: Metal-enhanced Fluorescence Effect Of Hms-ag-r and Hms-au-rmentioning
confidence: 96%
“…17 Além disso, o diâmetro reduzido desses materiais facilita a sua entrada no interior das células, possibilitando uma série de diagnósticos, imageamentos e tratamentos intracelulares. 18 Diversos compostos podem ser incorporados às partículas de ouro agregando propriedades específicas destes compostos no material. 19 Por essa razão, nanopartículas de ouro, modificadas ou não, possuem aplicação em diversas áreas como óptica, eletrônica, magnética e catálise.…”
Section: Introductionunclassified
“…It has also been shown that the lifetime of the excited state of an emitter located near a nanostructure is affected by the radiative decay rate due to photon emission and by the nonradiative decay rate due to energy dissipation in the environment. Furthermore, both of these rates can be enhanced [2][3][4][5][6][7][8][9]. This results in the possibility of using quant um emitters as ideal near-field sensors around plasmonic nanostructures, and this important application has been verified experimentally [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%